Geophysical analysis on electrical resistivity technique toward composite of geostrata - M. N., Noorasyikin; M., Zainab (RMP Publications, 2022)
Primarily geophysical techniques are the most widely used method that considers the safety, cost, and time-saving aspects. There are several techniques of geophysical techniques such as electrical resistivity, seismic, magnetic and ground penetrating radar. Among of the geophysical techniques, electrical resistivity is the best technique to detect subsurface abnormalities such as mine void; fractures, water level, and it can also identify the types of materials as either soil or rock. In this study, a laboratory model study of tank was carried out with different layers of geostrata. A forty-one of 15cm copper electrodes were set up in the tank at 0.04 meter spacing and Wenner protocol was applied. The main objectives of this study are to determine the 2D georesistivity profiling of stratified soil and hard layers. Based on observation, it was found that the georesistivity of materials were depending on several parameters such as moisture content, porosity and mineralogy.